SINERGITAS PENDAMPING HUKUM DAN UNIT PENJAGA TAHANAN DALAM MENJAGA TERJADINYA TINDAK PIDANA PENGANIAYAAN ANTAR WARGA BINAAN LAPAS KELAS IIA BAUBAU - Abdullah, La Ode Dedi; Tri Pratiwi, Endang; Abdullah, Rudi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
The result is the first: in dealing with the violence that has occurred against fellow citizens, the social security agencies are engaged in preventive and repressive efforts, such as interacting with the civilians, improving surveillance and construction, socializing human rights values in construction, giving day leave, conditional leave, family visiting leave, and conditional release. And second: The inhibitory factors of the Marketing Institute in counteracting the violence committed by the prisoners at the IIA Baubau Marketing Institute are: 1) the formation of a ruling group, 2) the interconnection between the builders, 3) the number of builders exceeding the capacity, where the number is 1538 builders while the residential capacity is 477 people, 4) the lack of number of officers that secure Lapas.